Efikasi Herbisida IPA Glifosat Terhadap Gulma Dan Dosis Pupuk (Urea+Sp-36+Kcl) Terhadap Pertumbuhan Kelapa Sawit Pada Fase Tanaman Belum Menghasilkan - Teddy Alfandi; Ardi; Zahlul Ikhsan (Jurusan Budidaya Perkebunan, 2021)
Weed control is one of the determining factors for achieving high oil palm yields, at the same time fertilization is necessary to provide nutrients for plants. This study aims to: (1) determine the interaction between the herbicide IPA Glyphosate with fertilizer Urea+SP-36+KCl on weed control and growth of immature oil palm. (2) to obtain an effective dose of herbicide to control weeds, and to obtain the best dose of Urea+SP-36+KCl fertilizer for the growth of oil palm. The study was conducted using a factorial Randomized Block Design (RBD) consisting of 2 factors and 8 treatment combinations. The first factor is herbicide doses of IPA Glyphosate (1,920 g/ ha, 2,400 g/ha, mechanical weeding, and control) and the second-factor is fertilizer doses of Urea+SP-36+KCl (600 g Urea +750 g SP-36 +700 g KCl/plant, and 700 g Urea + 850 g SP- 36 + 800 g KCl/plant). The data were analyzed for variance and if significantly different then continued with Duncan’s New Multiple Range Test (DMNRT) at the 5% level. The results showed that there was no interaction between the dose of the herbicide IPA Glyphosate with fertilizer Urea+SP-36+KCl on weed control and growth of immature oil palm. The herbicide dose of I PA Glyphosate which was effective in suppressing the dry weight of weeds was 1,920 g/ha because it was effective in suppressing the dry weight of weeds up to 12 weeks after application (WAA) and obtained the smallest average of weed dry weight. Urea+SP-36+KCl fertilizer application did not affect the vegetative growth parameters of immature oil palm.